Physics of diffuse optical imaging - Uluç, Nasire. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2012., 2012)
Diffuse optical tomography (DOT) is a functional imaging modality which con- sists of transilluminating of a volume. This diagnosis technique is particulary useful for characterizing thick tissue especially for breast tissue. By using model based im- age reconstruction, DOT provides us with the map of tissue properties such as total hemoglobin concentration and blood oxygen saturation via absorption coe±cient. Be- sides the image of the absorption property of the interior of the breast, DOT gives information about cellular and subcellular changes with the aid of scattering coe±- cient. Even though DOT is relatively low cost, non-invasive, and capable of measuring tissue hemodynamics, it has a drawback of having insu±cient spatial resolution be- cause of the nature of light when scattered in tissue. Therefore, the accuracy of the recovered optical parameters of the tissue is limited. In this thesis, the theoretical basis of diffuse optical spectroscopy and tomography is outlined. First, this thesis examines the theory of the propagation of light in tissue. Subsequently, it describes theoretical background of the image reconstruction of diffuse optical spectroscopy and tomogra- phy. Finally, the concepts of dual modality and pharmacokinetics model which play an important role in improvement of DOT are presented by using some fundamental techniques and methods.
Keywords: Optical tomography.; Optical spectroscopy.; Diagnostic imaging.; Imaging systems in medicine.